TECHNICAL AND VOCATIONAL EDUCATION UNIVERSITY STUDENTS’ CAREER DECISION SELF-EFFICACY: EXPLORING DEMOGRAPHICS IMPLICATIONS (NAU Journal of Technology and Vocational Education, 2024)
While university students of technical and vocational education must transit smoothly fromschool to work, inquiries patterning the students' career decisions appear relatively understudied;especially concerning demographic possibilities in predicting their career decision self-efficacy(CDSE). This paper explores the students' CDSE and the implications of their demographics(sex, academic major, and age) on their career decision self-efficacy (self-appraisal, occupationalinformation, goal selection, planning, and problem-solving). Adopting a correlational surveyapproach, the participants were 451 university students in technical and vocational educationfrom three geopolitical zones in Nigeria. The adopted CDSE scale used for this study showed agood model fit for its construct validity as well as high-reliability coefficients. Mean, standarddeviation, bivariate correlation, t-test, and multiple linear regression statistics were applied fordata analyses. Findings revealed that the students possessed some level of appreciable CDSE.Findings of multiple regression analysis revealed that academic major (Agricultural, Business,Home Economics, and Technical Education) has a relative association with CDSE. Meanwhile,the results also showed that the demographics have significant joint association withoccupational information, goal selection, planning, and problem-solving; but not self-appraisal.
Keywords: Career decision, demographics, self-efficacy, technical education, vocational education.